TEACHING THE TECHNIQUE OF BALL HANDLING IN BASKETBALL EFFECTIVENESS OF ENHANCING ACTIVITY - Dadabayev R. R. (Web of Journals Publishing, 2024)
The modern level of basketball development requires a lot of changes in the process of improving technical and tactical methods, which are closely related to the manifestation of special physical qualities and, in particular, to the level of their speed-power training.
Keywords: Modern basketball, top category, technique and tactics, pedagogical observation, to the basket the ball throwing, sprinting.